Significance of Functional Status Scale in decannulation after pediatric tracheostomy: A single-center, retrospective study - Taylor B. Teplitzky; Nicholas Paul Randolph; Ji Li; Kevin D. Pereira; Mathangi Gopalakrishnan; Adrian Holloway (Journal of Pediatric Critical Care)
Background: Metrics to successfully predict pediatric decannulation have been ineffective. The Functional Status Scale (FSS) is a validated pediatric scoring system of functional outcomes. The objective of this study was to evaluate if the FSS over time predicts pediatric tracheostomy decannulation. Subjects and Methods: Chart review of patients admitted to the pediatric intensive care unit (PICU) and underwent tracheostomy at a tertiary care children’s hospital from 2010 to 2019. Baseline demographics, comorbidities, tracheostomy indication, decannulation status, and FSS scores were recorded at PICU discharge and 1 and 3 years after tracheostomy. Logistic regression was performed to assess the association of FSS components with decannulation status at 3 years. Results: Fifty-three patients met the inclusion criteria. Forty (75.5%) patients had complete data. There were no decannulations at 1 year. Nine (22.5%) patients were decannulated at 3 years. An abnormal 3-year FSS score in the feeding domain was significantly associated with persistent tracheostomy at 3 years, with an odds ratio of 7.4 (95% confidence interval: 1.5–36.6, P = 0.01). Conclusions: FSS score can predict decannulation in children discharged from the PICU. This information could modify caregiver expectations and guide rehabilitative efforts.